Analysis of Students Mathematical Reasoning Abilities in Terms of Self-Regulated Learning - Hella Jusra; Anisa Dita Rahmawati (Universitas Kanjuruhan Malang, 2022)
The implementation of research activities in this paper is intended to provide an analysis related to the ability of students to reason mathematically in terms of self-regulated learning using qualitative methods and descriptive approaches. Data collection techniques will be obtained through filling out 6 test questions, 28 questionnaire statements, and interview activities. The subjects to be observed were carried out through a technique called purposive sampling so that 6 students were obtained which were divided into two students in each category. The datta will be arranged sequentially using data analysis technique consisting of data reduction, data presentation, and drawing conclusions. The results of the data found identify that students in the high self-regulated learning category have mathematical reasoning abilities as well. Furthermore, students in the medium categori have the ability to do moderate mathematical reasoning. Finally, students who are in the low category have low mathematical reasoning abilities. So based on the data above, it can be concluded that the higher the level of self-regulated learning. The less likely it is to make mistakes in solving problem related to the ability to do mathematical reasoning. The gives an indication that the better the level of intelligence and critical thinking that a person has, the mathematical reasoning ability will follow in the same.